Service Facilities and Spatial Development: A Study on Rangpur City Corporation Area, Bangladesh - Md. Kamrul Hasan; Mehruna Tabassum; Sharmin Aktar Shimu (Department of Urban and Regional Planning, Universitas Diponegoro, 2021)
Inadequate and Inequall service distribution is one of the primary problems in a city. Bangladesh's main cities are presently faced with significant urban population expansion, and urban expansion is resulting in many unplanned developments. One of Bangladesh's most rapidly rising cities is the Rangpur City Corporation (RpCC) area. As the population in the city is growing rapidly, the city has pressure to provide service facilities in the area with heavier population demand. The city corporation is now separated into two primary land uses - core and non-core according to existing conditions of service. The research aims to identify the nature of the spatial distribution of service facilities (schools, colleges, health care centers, mosques, temples) and to analyze the deficiencies of different service facilities in both core and non-core areas of Ranpur City Corporation. The research is mainly based on primary data collected by a questionnaire survey from the authority of RpCC. In this research, the requirements and the deficiency of different amenities are also calculated using population projections by arithmetic increase method and population coverage of each service facility. The calculation found that the shortfall of service facilities are higher in the non- core area than the core area of RpCC, and major markets are concentrated in the core area. This type of centralization can create pressure on the resources of a core area. The identified nature of centralization from the study can be used for future planning and development of service facilities to ensure proper distribution in RpCC area.